Atividade antiproliferativa da chalcona (e)-1-(4-aminofenil)-3-(2,2-difluorobenzo[d][1,3]dioxol-5-il)prop-2-en-1-ona em Trypanosoma cruzi: uma abordagem in silico e in vitro - Nunes, João Victor Serra (2024)
Chagas disease (CD), endemic in 20 Latin American countries, affects 7 million people worldwide, causes approximately 14,000 deaths annually, and puts more than 75 million people at risk of infection. The only available treatment, with Benzonidazole, has various limitations and contraindications, making the development of new therapeutic agents urgent. This study describes the synthesis, characterization, and inhibitory effects of the chalcone (E)-1-(4-aminophenyl)-3-(2,2-difluorobenz[d][1,3]dioxol-5-yl)prop-2-en-1- one (DF) against forms of Trypanosoma cruzi of the Y strain. The molecular structure of this compound was characterized by spectrophotometry and flow cytometry, and its potential against T. cruzi was evaluated through in vitro and in silico assays. The results of this study showed that the chalcone exhibited trypanocidal effects and reduced toxicity compared to Benzonidazole (reference). Furthermore, it induced morphological changes such as cell leakage and pore formation on the parasite surface, observed via scanning electron microscopy and corroborated by flow cytometry results using 7-AAD staining, indicative of necrosis, with better selectivity compared to Benzonidazole. Modeling results showed a high affinity of the chalcone ligand with the enzyme Cruzaine, crucial for the metabolism and life cycle of T. cruzi, forming a stable complex interacting at the same site as the inhibitor KB2 (ligand co-crystallized in the enzyme Cruzaine). The ADMET study demonstrated that the chalcone possesses size, lipophilicity, and polarity properties that favor its membrane permeability. These results are relevant since chalcones have been described as molecules with potential to inhibit growth or cause death of T. cruzi. In conclusion, the chalcone (E)-1-(4-aminophenyl)-3-(2,2- difluorobenz[d][1,3]dioxol-5-yl)prop-2-en-1-one (DF) enhances prospects for the development of new therapeutic agents.